2012
DOI: 10.1016/j.jacc.2011.11.038
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intervention Prevents Dyslipidemia Associated With Highly Active Antiretroviral Therapy in Human Immunodeficiency Virus Type 1–Infected Individuals

Abstract: Among HIV-1-positive individuals naive of previous treatment, diet prevents dyslipidemia associated with HAART. (Effect of Nutritional Intervention on the Lipid Profile of HIV-Positive Patients Who Start HAART: a Randomized Trial; NCT00429845).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0
10

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 29 publications
2
57
0
10
Order By: Relevance
“…The use of lipidlowering therapy was low and similar among centers, but no dietary intervention had been provided, even though there is evidence of benefit equivalent to lipidlowering agents [37]. Although the frequency of physical inactivity was much higher in Recife, the effectiveness of physical activity in improving the lipid profile in HIV-infected patients in routine conditions is still unclear [38].…”
Section: Discussionmentioning
confidence: 99%
“…The use of lipidlowering therapy was low and similar among centers, but no dietary intervention had been provided, even though there is evidence of benefit equivalent to lipidlowering agents [37]. Although the frequency of physical inactivity was much higher in Recife, the effectiveness of physical activity in improving the lipid profile in HIV-infected patients in routine conditions is still unclear [38].…”
Section: Discussionmentioning
confidence: 99%
“…According to Lazzaretti et al 22 , the risk of development of dyslipidemia in PLH with the use of ART in Brazil may be 70%. A Brazilian study evaluated PLH with and without the use of ART and observed significantly higher values of TC, LDL-c and TG in the population with the use of ART, illustrating the importance of identification of metabolic disorders before the initiation of ART, and adopting a multidisciplinary approach in this population with the aim of lifestyle modification 23 .…”
Section: Discussionmentioning
confidence: 99%
“…However, a very Citation: Spagnuolo MI, Liguoro I, Guarino A (2014) Metabolic Disorders in HIV-infected Children Metabolic Disorders in HIV-infected Children. J recent randomized study evaluated patients who had just begun HAART and prescribed a hypocaloric diet and were strictly followed, while controls had no diet and no nutritional follow-up [175]. This kind of approach resulted to prevent HAART-related dyslipidemia and lipodystrophy.…”
Section: Hiv and Dyslipidaemiamentioning
confidence: 99%